Failure analysis of fiber reinforced composite materials used in Malaysian industries / Jamaluddin Mahmud, Wahyu Kuntjoro and Aidah Jumahat - Mahmud, Jamaluddin; Kuntjoro, Wahyu; Jumahat, Aidah (Institute of Research, Development and Commercialisation (IRDC), 2007)
The main objective of this paper is to determine the curves bounding the actual load carrying capacity in terms of the First Ply Failure and the Last Ply Failure of composite materials used in Malaysian Industries. A mathematical model and computational model are presented for the analysis. Higher Order Shear Deformation plate theory is employed to predict the deformation of the plate. The selected material properties through thickness is used and accommodated by a discrete layer approach. A program based on finite element method is developed using Fortran-90 to determine the lamina stresses. These stresses are then used in the present failure model to determine the First Ply Failure and Last Ply Failure, by progressively reducing the stiffness of the laminas. Finally, the First Ply Failure and Last Ply failure results are analysed, in terms of lower and upper bound within which the true load carrying capacity lies.